1975
DOI: 10.1039/p19750001682
|View full text |Cite
|
Sign up to set email alerts
|

The structures of D-arabinose and D-glucose oximes

Abstract: marabinose oxirne, m.p. 156-137*, which consist of a mixture of SYS-(80%) a d uMS-(20%) forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 0 publications
1
21
0
Order By: Relevance
“…In accordance with previously reported spectroscopic data, [18b,23,25] for glucose conjugates of N-methylhydroxylamines, we found that the conjugates Bz(M-AE)-Glc and Ac(M-AMB)Glc were obtained in the 4 C 1 conformation with complete diastereoselectivity as β-pyranose forms. Also compound Boc(AMB)Glc, was in agreement with our prediction [28] as NMR spectroscopic analysis revealed the presence of both open-chain and ring-closed tautomers as follows: (E)-oxime/(Z)-oxime/β-pyranose ringchain in 60:20:20 ratio respectively. No structural characterization has been previously reported in the literature concerning conjugates between carbohydrates and N-benzylhydroxylamines.…”
Section: Resultssupporting
confidence: 89%
“…In accordance with previously reported spectroscopic data, [18b,23,25] for glucose conjugates of N-methylhydroxylamines, we found that the conjugates Bz(M-AE)-Glc and Ac(M-AMB)Glc were obtained in the 4 C 1 conformation with complete diastereoselectivity as β-pyranose forms. Also compound Boc(AMB)Glc, was in agreement with our prediction [28] as NMR spectroscopic analysis revealed the presence of both open-chain and ring-closed tautomers as follows: (E)-oxime/(Z)-oxime/β-pyranose ringchain in 60:20:20 ratio respectively. No structural characterization has been previously reported in the literature concerning conjugates between carbohydrates and N-benzylhydroxylamines.…”
Section: Resultssupporting
confidence: 89%
“…[8] Additionally, Nmethyl substituted aminooxy derivatives have been pursued. [9,28] Carbohydrate oximes and oxime ethers are known to exist in several ring-chain tautomeric forms, [29] of which the open-chain E and Z forms generally predominate over the pyranose b and a forms, [30][31][32] as shown for d-glucose in Scheme 1. Additionally, furanose b and a forms may constitute minor tautomers (not shown).…”
Section: Introductionmentioning
confidence: 98%
“…An exception is glucose, from which the E-and Z-open-chain oximes 10 and 11 and the Nb-d-glucopyranosylhydroxylamine 12 have been prepared (Scheme 1). [34][35][36][37][38] Recently, the synthesis of a cyclic N-b-d-xylofuranosylhydroxylamine has been reported. [39] We prepared the crystalline compound 12 (yield 82 %) by stirring glucose with hydroxylamine in dry methanol at 20-25 8C.…”
Section: Resultsmentioning
confidence: 99%